A Multilevel Investigation of Leadership and Turnover Behavior. (September 2015) - Waldman, David A.; Carter, Min Z.; Hom, Peter W.
This study extends the sparse research on the connection between leadership and follower turnover by investigating the effects of group-level transformational leadership on the withdrawal process. Through an examination of 375 Chinese employees from 96 work groups, we used hierarchical generalized linear modeling (HGLM) analyses to test our proposed model. Findings reveal that, even when we control for the effects of leader–member exchange and contingent reward leadership, transformational leadership predicts turnover through quit intentions. In addition, our test of cross-level moderation reveals that transformational leadership can weaken the effect of quit intentions on turnover. Thus, employees are less likely to carry out quit intentions when they have transformational leaders.